Fault-tolerant task scheduling in multiprocessor systems - Bertossi, Alan A.; Mancini, Luigi V. (1991)
Abstract: "Minimizing the finish time of a set of independent tasks executed on a multiprocessor system, where no faults occur, is a well-known NP-complete problem. However, an approximated schedule can be found efficiently by means of the so called Largest Processing Time (LPT) rule. The above scheduling problem extended to faulty environments may seem daunting. However, this paper shows how to extend the LPT rule in a fault-tolerant Non-Uniform-Memory-Access (NUMA) multiprocessor employing a primary copy and a backup copy for each task in order to handle processor failures. The notion of expected schedule length is also introduced to evaluate the performance of the resulting schedule in case of processor failures
Keywords: Fault-tolerant computing; Multiprocessors